If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 8) + 9 = 3 + 4x Reorder the terms: 2(8 + 3x) + 9 = 3 + 4x (8 * 2 + 3x * 2) + 9 = 3 + 4x (16 + 6x) + 9 = 3 + 4x Reorder the terms: 16 + 9 + 6x = 3 + 4x Combine like terms: 16 + 9 = 25 25 + 6x = 3 + 4x Solving 25 + 6x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 25 + 6x + -4x = 3 + 4x + -4x Combine like terms: 6x + -4x = 2x 25 + 2x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 25 + 2x = 3 + 0 25 + 2x = 3 Add '-25' to each side of the equation. 25 + -25 + 2x = 3 + -25 Combine like terms: 25 + -25 = 0 0 + 2x = 3 + -25 2x = 3 + -25 Combine like terms: 3 + -25 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| 2t^2+10t+3=0 | | -1/12-7/12 | | 4-7y+5=2y+11-7y | | -3/4=x/3 | | x*y=240 | | x*y=250 | | a/9-15 | | -2a/3=-3/4 | | 4(x-5)-3(x-2)=1 | | c=180+65h | | (11-7)+g= | | 4-(4-4k)=-10-16 | | 35=w+7 | | 38=-11a-a^2 | | 3/4w=1/5 | | 15=7.5 | | 11v^2-15v+132=10v^2 | | 6(x+-1)=2+8x | | x/1.2=5 | | x+1/2-1=7 | | 3x-15/3=5 | | 48+9(y-7)= | | x/3.7=2.1 | | 3x-7+2x=13 | | 3x/2-3=3 | | 2n^2+12n+36=-7 | | m+(-4.4)=-3.6 | | (3+4x)(5+6x)= | | 4-6x=3x+11 | | 2.1*4.1= | | 0.5x^2+x+0.5=0 | | 3(x-5)+8=-(2-x)-25 |